Penerapan Sistem Sirkulasi Perpustakaan Berbasis Slims Pada SMA IT Al Fityah Pekanbaru - Loneli Costaner; Guntoro; Yuhelmi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
In the world of education there is now an electronic-based learning system that can be used for distance learning. The change in learning from the manual base to electronic precisely the internet indicates a global change to make it easier for humans to interact without having to meet. In the field of computers today we also find many companies in the company, the market and the world of education, including schools, have used information systems based on automation. With the aim of facilitating the processing of data and information can be obtained quickly and accurately. One way to provide good, fast and safe service is a trusted and proven system that is able to provide librarian officers with an open source SLIMS application. SLIMS is an application library that is almost perfect for organizing data data and information needed.